Liturgical Irenicism and the Unity of the Church - Smith, Innocent (New blackfriars, 2015)
The liturgy has often been a source of conflict within Christian communities. After comparing several recent exhortations by Pope Francis and Pope Emeritus Benedict XVI concerning the importance of the unity of the Church, this essay examines resources for articulating an approach of “liturgical irenicism” on the basis of texts from Augustine, Thomas Aquinas, and the Magisterium of the Church.